Acceptance of Low Vision Aids in Visually Impaired Patients Attending to Tertiary Eye Hospital, Nepal - Adhikari, Pankaj Ray; Khanal, Miru; Chaudhary, Nirmala; Chaudhry, Monica; Anwar, Afaque; Karn, Rajiv Ranjan (Birat Journal of Health Sciences, 2020)
Introduction: Vision impairment is the degree of reduction in vision that makes a remarkable effect on personality, intelligence, social, mental and economic factors of individuals. Objective To analyze the acceptance of low vision aids with their respective occupations and needs in visually impaired patients atiending to Tertiary Eye Hospital. Methodology A cross-sectional study was done at the low vision clinic of Biratnagar Eye Hospital (BEH), Biratnagar, Nepal from January to March 2018. During the study period, a total of 51 visually impaired patients were included for the study who were eligible and willing to participate. Result The most common age group visited to low vision clinic were up to 20 years (43%). Males comprised a maximum study population of (88%) and most of them were from the neighboring country India (96%). The most common disease-causing low vision was Retinal Diseases (41%). Among all occupations, students accepted more optical low vision aids for both distance(31.5%) and near (47%). The most common demand was reading and writing (86%). At distance, the telescope was prescribed to (65%) and at near, spectacle magnifiers were prescribed to (72%). Conclusion: There is more acceptance of the low vision aids among the students for both distance and near work compare to other occupation. The low vision device should be prescribed concerning the education, occupation, and needs of the patients.